THE USE OF RAFT STRATEGY TO IMPROVE THE STUDENTS’ WRITING ABILITY - Amroh Umaemah; Mohammad Adnan Latief; Eny Irawati (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2016)
Abstract: Teaching English writing for the students of junior high school level needs high creativity, the students have to be encouraged to study hard to gain writing competence. Additionally, the students themselves face many problems: the lack of vocabulary and poor knowledge of grammar. The objective of the study is to improve the students’ writing ability using RAFT strategy employing classroom action research (CAR) design involving two cycles, three meetings each. The observation to see the result of the implementation used questionnaire, observation checklist, writing test and field notes. The expected criteria of success were that all the students achieve the minimum passing grade 55 and 75% of them involve actively in the implementation of the RAFT strategy. Thirty students of grade 8 of MTs Salafiyah Syafiiyah Babakan Ciwaringin Cirebon West Java participated in the study. The finding shows the implementation of RAFT strategy was successful to improve the students’ writing ability. All the students achieved the score at least 55 and 74.24% of them actively involved in the process of teaching and learning.  Key Words: RAFT strategy, improve, writing, ability.